The Social Status of a Teacher in Selected School Policy Programme Documents in the Slovak Republic - Plavčan, Peter
Selected findings on financing the education. Salaries of teachers. Programme statements of the Government of Slovak Republic from 1992, National Program of Education Project Constantine from 1994, National Programme of Education in the Slovak Republic for the next 15 - 20 years Millenium from 2002 and the National Programme for the Development of Education for the Years 2018 - 2027 Learning Slovakia from 2017.